Rice starch and seaweed biopolymer blends for transformative food applications - Pascua, Noel C.; Tiozon, Rhowell Jr. N.; Ong, Glenn Vincent P.; Jose, Jhaymes Khylle V.; Roleda, Michael Y.; Sreenivasulu, Nese (Informa UK Limited, 2025)
Rice is one of the most widely consumed foods globally, while seaweed is gaining popularity due to its exceptional nutritional composition, which includes vitamins, minerals, dietary fiber, unsaturated lipids, and antioxidants. Besides being vital contributors to global food and nutrition security, rice and seaweeds are sources of industrially important biopolymers such as starch, alginates, carrageenan, and agar. In this review, we compiled studies pertaining to the health impacts of rice and seaweed food production mechanisms by aligning them with planetary and human health benefits. We emphasized the importance of nutritional, physicochemical, and functional properties of the composites of rice starch and algal-derived hydrocolloids for a wide range of food applications. These include the blending of rice starch with hydrocolloids to produce an array of products like edible film coatings with enhanced solubility and barrier properties; microcapsules with greater protective capacity; noodles with improved texture and digestibility; and modified starch which could be applied in various products including baked goods were highlighted. Rice-based foods fortified with seaweeds exhibited improved health-promoting effects such as higher dietary fiber content, higher antioxidant activity, and strong anti-diabetic potential were discussed.